The Northwest Participant and Clinical Interactions Network: Increasing opportunities for patients to participate in research across the Northwestern United States. Issue 2 (19th April 2017) - Baldwin, Laura-Mae; Hassell, Laurie; Laukes, Cindi; Doyle, Michelle; Reedy, Anne; Mollis, Brenda; Albritton, Sandra; Ciemins, Elizabeth; Coker, Robert; Brant, Jeannine; Tuttle, Katherine R.; Baker, Laura; et al.
Abstract : Introduction: The Institute of Translational Health Sciences (ITHS) promotes and supports translational research collaboration between clinicians, communities, and investigators across the five-state Washington, Wyoming, Alaska, Montana, and Idaho (WWAMI) region. The ITHS has developed a collaborative regional clinical research network, the Northwest Participant & Clinical Interactions Network (NW PCI), involving 12 diverse clinical health systems and academic institutions. Methods: This descriptive article details NW PCI's development, infrastructure and governance, tools, characteristics, and initial outcomes. Results: Regional NW PCI sites are conducting largely industry-sponsored studies; they are interested in including more grant-funded research. Regional NW PCI sites had over 1, 240 open studies involving over 6700 patients in 2016. NW PCI trials are largely industry-sponsored; NW PCI sites are interested in including more grant-funded research. In its first three years, the NW PCI Coordinating Center facilitated regional sites' participation in 34 new grant and contract applications across diverse topics. Conclusion: The NW PCI model supports the goals of the developing CTSA Trial Innovation Network by increasing access to cutting-edge research across the Northwestern U.S., by supporting investigators seeking diverse populations, including those with rare diseases, for their research studies, and by providing settings to test implementation and dissemination of effective interventions.